Supply or demand? Institutionalization of the mentally ill in the emerging Swedish welfare state, 1900–59. Issue 2 (June 2022) - Eriksson, Liselotte; Junkka, Johan; Sandström, Glenn; Vikström, Lotta
Historical studies on the institutionalization of the mentally ill have primarily relied on data for institutionalized patients rather than the population at risk. Consequently, the underlying factors of institutionalization are unclear. Using Swedish longitudinal microdata from 1900–59 reporting mental disorders, we examine whether supply factors, such as distance to institutions and number of asylum beds, influenced the risk of institutionalization, in addition to demand factors such as access to family. Institutionalization risks were associated with the supply of beds and proximity to an asylum, but also dependent on families' unmet demand for care of relatives. As the supply of mental care met this family-driven demand in the 1930s, the relative risk of institutionalization increased among those lacking family networks.